Gut microbiome as a potential mediator linking sexual behaviors to immune profiles in HIV-negative men who have sex with men: a multi-omics study - Li, Kangjie; Zeng, Haijiao; Liu, Tian; Huo, Siyan; Zhang, Cong; Li, Wenlong; Deng, Jielian; Zhong, Xiaohua; Tao, Yi; Lin, Bing; Liu, Jiaxiu; Xie, Biao; et al. (Frontiers in Immunology, 2025)
IntroductionThe effects of sexual behaviors on the gut microbiome and immune system in men who have sex with men (MSM) remain unclear. Here, we conducted a multi-omics study in MSM to investigate how sexual behaviors shape gut microbiome composition and immune profiles in this population. The interplay among high-risk sexual behaviors, gut microbiome, and systemic immune activation was also explored.MethodsHIV-negative MSM were enrolled in this study. Fecal samples were collected and subjected to 16S rRNA gene sequencing. Bulk and single-cell transcriptome sequencing of peripheral blood mononuclear cells (PBMCs) were performed to investigate the systemic immune profiles. Primary component analysis and spearman correlation analysis were used to assess the associations between gut microbiome and immune signatures. BayesPrism algorithm was applied to predict cellular composition and gene expression in individual cell types by integrating bulk RNA sequencing and sc-RNA sequencing. Causal mediation analysis evaluated the contribution of gut microbiome in linking sexual behaviors to immune outcomes.ResultsThe gut microbiome of HIV-negative MSM was dominated by Segatella. Receptive anal intercourse had the most significant impact on the gut microbiome, characterized by increased diversity, depletion of Xylanibacter, and enrichment of Holdemania. We also identified altered immune gene expression, an elevated CD8:CD4 ratio, distinctive CD4+ T cell communications, and higher expression of CXCR4 in CD4+ T cells in MSM engaged in receptive anal intercourse. Mediation analysis indicated that Bilophila potentially mediated the effects of receptive anal intercourse on CD4+ T cell proportions (P = 0.026). MSM exposed to group sex and illicit drug had elevated HIV susceptibility index, possibly mediated by Bifidobacterium (P = 0.012, P = 0.02 respectively).ConclusionOur study indicates that gut microbiome partially mediates the immunomodulatory effects of sexual behaviors, providing mechanistic insights into HIV susceptibility. These findings underscore the gut-immune axis as a potential target for HIV prevention strategies in high-risk MSM.